Pleiotropic Functions of Nitric Oxide Produced by Ascorbate for the Prevention and Mitigation of COVID-19: A Revaluation of Pauling’s Vitamin C Therapy - Hideo Yamasaki; Hideyuki Imai; Atsuko Tanaka; Joji M. Otaki (Microorganisms, 2023)
Linus Pauling, who was awarded the Nobel Prize in Chemistry, suggested that a high dose of vitamin C (l-ascorbic acid) might work as a prevention or treatment for the common cold. Vitamin C therapy was tested in clinical trials, but clear evidence was not found at that time. Although Pauling’s proposal has been strongly criticized for a long time, vitamin C therapy has continued to be tested as a treatment for a variety of diseases, including coronavirus infectious disease 2019 (COVID-19). The pathogen of COVID-19, SARS-CoV-2, belongs to the β-coronavirus lineage, which includes human coronavirus, severe acute respiratory syndrome (SARS), and Middle East respiratory syndrome (MERS). This review intends to shed new light on vitamin C antiviral activity that may prevent SARS-CoV-2 infection through the chemical production of nitric oxide (NO). NO is a gaseous free radical that is largely produced by the enzyme NO synthase (NOS) in cells. NO produced by upper epidermal cells contributes to the inactivation of viruses and bacteria contained in air or aerosols. In addition to enzymatic production, NO can be generated by the chemical reduction of inorganic nitrite (NO2−), an alternative mechanism for NO production in living organisms. Dietary vitamin C, largely contained in fruits and vegetables, can reduce the nitrite in saliva to produce NO in the oral cavity when chewing foods. In the stomach, salivary nitrite can also be reduced to NO by vitamin C secreted from the epidermal cells of the stomach. The strong acidic pH of gastric juice facilitates the chemical reduction of salivary nitrite to produce NO. Vitamin C contributes in multiple ways to the host innate immune system as a first-line defense mechanism against pathogens. Highlighting chemical NO production by vitamin C, we suggest that controversies on the therapeutic effects of vitamin C in previous clinical trials may partly be due to less appreciation of the pleiotropic functions of vitamin C as a universal bioreductant.